Job creation and job destruction in Estonia: labour reallocation and structural changes - Jaan Masso; Raul Eamets; Kaia Philips (Institute for the Study of Labor (IZA), 2005)
This article documents and analyses gross job flows and their determinants in Estonia over the years 1995-2001, using a database containing the population of officially registered firms in Estonia (all in all 52,000). Our results show that job creation and job destruction rates have been rather high in Estonia and are comparable to the levels documented for the US. We find that the firm-specific component in job flows excess of employment change had relatively lower importance than in western studies due to the emergence of small and medium-sized enterprises and labour reallocation between the economic sectors. The high inter-sectoral mobility has helped maintain high levels of job flows, while both are high also due to a favourable institutional environment, especially due to low start-up costs and a large share of micro enterprises in Estonia. When investigating job creation and destruction at the firm level by estimating firms' growth equations, we detected a negative effect of their size and age on the growth of firms, especially of domestic firms. The job flows have not decreased recently, although worker flows have dropped. One explanation is provided by labour market institutional framework, while the other one relates to the concept of churning flows (the difference between worker and job flows).
Keywords: J6; P2; L11; 330; job creation; job destruction; worker flows; churning flows; Estonia; Arbeitsmarkt; Beschäftigung; Arbeitsmobilität; Estland